Are People Experiencing the ‘Pains of Imprisonment’ During the COVID-19 Lockdown? - Dhami, Mandeep K.; Weiss-Cohen, Leonardo; Ayton, Peter (Frontiers in Psychology, 2020)
Background: By the end of March 2020, more than a fifth of the world’s population was in various degrees of ‘lockdown’ in order to slow the spread of Covid-19. This enforced confinement led some to liken lockdown to imprisonment. We directly compared individual’s experiences of lockdown with prisoners’ experiences of imprisonment in order to determine whether psychological parallels can be drawn between these two forms of confinement. Method: Online surveys of adults in lockdown in the UK (N = 300) and California (N = 450) were conducted four and five weeks into lockdown in each region, respectively. The UK data was then compared to Souza and Dhami’s (2010) sample of 267 medium security prisoners in England, and the Californian data was compared to Dhami et al.’s (2007) sample of 307 medium security Federal prisoners in California. We measured the effects of Group (Lockdown v. Prison) on five categories of dependent variables (i.e., activity, social contact, thoughts, feelings, and rule-breaking), controlling for demographic differences between the groups. Results: In both regions, people in lockdown thought significantly less often about missing their freedom, as well as missing their family and friends living elsewhere than did first-time prisoners. However, people in lockdown in both regions were also significantly less engaged in a range of daily activities than were first-time prisoners. Additionally, in both regions, people in lockdown reported feeling more hopeless than first-time prisoners. Conclusions: Although Governments introducing lockdown policies do not intend to punish their citizens as courts do when sending convicted offenders to prison, such policies can have unintended adverse consequences. Psychological parallels can be drawn between the two forms of confinement, and ordinary citizens in lockdown have, to some extent, sensed the ‘pains of imprisonment.’